PERBAIKAN TATA LETAK PENYIMPANAN BARANG DI GUDANG UNTUK REDUKSI JARAK TEMPUH PERJALANAN MATERIAL HANDLING - WINANDA KARTIKA; AHMAD WIMBO HELVIANTO (Jurnal Manajemen Industri dan Logistik (JMIL), 2017)
Warehouse acts as distributor of the product to the consumer. This is done by PT.XYZ as warehouse outsourcing. PT. XYZ manage a number of beverage products manufactured by PT ABC. The problem faced is the warehouse has not had an arrangement regarding the layout of product placement so that the preparation is done randomly depending on the overall storage blocks are empty. Each block storage in this warehouse holds only one type of product and the expiration date, so that the placement of the goods must be in blocks that are empty and do not take into account travel distance of material handling in the store and pick up the goods. In addition, the product storage memory depends only on the operator alone. Therefore, it is necessary to redesign the product placement on the storage location of the performance criteria minimize the total travel distance of material handling. Proposed layout product placement implementing dedicated storage method is a method for solving the layout of the warehouse includes product placement in the warehouse based on the amount of activity out of the product in the warehouse with the shortest distance to I/O point. With the application of this method, it is expected the product to be stored occupies a fixed location to enable the operator to store and retrieve the product. Results from a dedicated application, obtained the total travel distance by 23719.36 m, while the total mileage of the existing condition of 27038.1 with the percentage of 12.27% decline